DAMPAK PERUBAHAN UPAH TERHADAP OUTPUT DAN KESEMPATAN KERJA INDUSTRI MANUFAKTUR DI JAWA TENGAH - Juhaari, Imam; Atmanti, Hastarini Dwi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The study arms to analyze the impact of changes in wages manufacturing sector’s output andemployment in the manufacturing sector in Central Java Province, and to analyze the manufacturingsector linkages with other sectors, both connections to the forward and backward linkages in CentralJava Province. To analyze the manufacturing sector linkages analysis used backward and forwardlinkages. While to analyze the impact of a wage increase manufacturing sector’s output and employment,the first step taken is to determine the amount of wage increase manufacturing sector which then serveas a shock. The second step is to analyze the influence of wage increases shock on output andemployment in the manufacturing sector in Central Java Province. In this study use Input Output tablesof Central Java in 2004. The result showed that 35 sub sectors in manufacturing industry sector basedon I_O tables of Central Java in 2004, 25 sub sectors have relevance to a larger rear. The increase inwages in manufacturing sector in 2005 led to the manufacturing industry sector in Central Java toincrease its output of 2,879,359.31 million dollars. The increase in output that occurs later will have animpact on increasing employment opportunities in manufacturing sector of 43,529 inhabitants.Keywords: impact of rising wages, the manufacturing industry.